2017
DOI: 10.5038/1827-806x.46.3.2105
|View full text |Cite
|
Sign up to set email alerts
|

Screening of antifungal susceptibility in cave-dwelling aspergilli and report of an amphotericin B-resistant Aspergillus flavus

Abstract: Abstract:Caves are stable environments that favour the development of several microorganisms.The aspergilli represent a large number of species isolated from caves including strains capable of causing serious invasive opportunistic infections in humans. Considering that caves may harbour resistant strains to many antibiotics, investigation on the response of opportunistic aspergilli, isolated from pristine and tourist caves to antifungal agents and the mechanisms involved in resistance might be clinically rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Detection of an amphotericin B resistant strain of A. flavus isolated from a cave in Brazil having a MIC value of 4 μg/mL supports this notion [132]. Though mechanisms of amphotericin B resistance is not known in A. flavus , it appears that it may be due to higher ergosterol levels and increased enzymatic activity of the peroxidase and superoxide dismutase, with lower lipid peroxidation [132].…”
Section: Antifungal Resistancementioning
confidence: 98%
“…Detection of an amphotericin B resistant strain of A. flavus isolated from a cave in Brazil having a MIC value of 4 μg/mL supports this notion [132]. Though mechanisms of amphotericin B resistance is not known in A. flavus , it appears that it may be due to higher ergosterol levels and increased enzymatic activity of the peroxidase and superoxide dismutase, with lower lipid peroxidation [132].…”
Section: Antifungal Resistancementioning
confidence: 98%
“…Although there is very little literature on A. flavus being responsible for endogenous Aspergillus endophthalmitis in immunocompetent individuals, this is well recognized for immunocompromised individuals. A clinical study showed a 23-year-old female presented with a history of taking steroids for the past year developing A. flavus endophthalmitis that led to sudden vision loss [ 57 ]. About 34% of trauma cases were associated with A. flavus endophthalmitis [ 13 ].…”
Section: Aspergillus Species and Endophthalmitismentioning
confidence: 99%
“…Diaz et al identified antibiotic resistance genes in three different habitats across a permafrost thaw gradient within a pristine Arctic wetland. Taylor et al found amphotericin B resistance in fungal Aspergilus spp. isolated from pristine caves in Brazil.…”
Section: Incidence Of Arbs In the Environment Foodstuffs And Clinical...mentioning
confidence: 99%